2007
DOI: 10.1086/521522
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Diagnostics of Starburst Galaxies: Clumpy, Dense Structures in Star‐Forming Regions in the Antennae (NGC 4038/4039)

Abstract: Recently, mid-infrared instruments have become available on several large ground-based telescopes, resulting in data sets with unprecedented spatial resolution at these long wavelengths. In this paper we examine 'ground-based-only' diagnostics, which can be used in the study of star-forming regions in starburst galaxies. By combining output from the stellar population synthesis code Starburst 99 with the photoionization code Mappings, we model stellar clusters and their surrounding interstellar medium, focusin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 56 publications
5
81
0
Order By: Relevance
“…5. the metallicity, the higher the age of the stellar population, and the higher the gas density, the lower should be the II] 12.81 line ratios are also lower in the center than around it. This ratio ranges between 0.002 and 0.013 in the center, which indicate densities larger than 10 6 cm −3 in a >5 Myr old starburst system with solar metallicity and relatively high (q = 8 × 10 8 ) ionization parameter (Snijders et al 2007, their 2)) are about ten times higher than the observed ratios. These can be a consequence of the about ten times higher extinction found in NGC 4945 than in the sample of galaxies used by PereiraSantaella et al (2010).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…5. the metallicity, the higher the age of the stellar population, and the higher the gas density, the lower should be the II] 12.81 line ratios are also lower in the center than around it. This ratio ranges between 0.002 and 0.013 in the center, which indicate densities larger than 10 6 cm −3 in a >5 Myr old starburst system with solar metallicity and relatively high (q = 8 × 10 8 ) ionization parameter (Snijders et al 2007, their 2)) are about ten times higher than the observed ratios. These can be a consequence of the about ten times higher extinction found in NGC 4945 than in the sample of galaxies used by PereiraSantaella et al (2010).…”
Section: Discussionmentioning
confidence: 66%
“…5), with the exception of NGC 7130, the only galaxy classified as LINER/Seyfert 2 in their sample. According to (Snijders et al 2007), the higher Fig. 11.…”
Section: Discussionmentioning
confidence: 97%
“…Rigby et al 2011, and references therein). Snijders et al (2007) shows that a geometrical model in which several individual starforming clumps are embedded in a giant molecular cloud can reproduce these extreme ISM conditions. We speculate that global spectra of our high redshift galaxies may be dominated by H II regions similar to the clumpy, dense star-forming regions in the Antennae and M82.…”
Section: Testing the Cosmic Bpt Diagrammentioning
confidence: 97%
“…More problematic is the fact that the models do not give a very good description of the observed spectrum of H ii regions. Snijders et al (2007) compared the MAPPINGS models with the observations of Giveon et al (2002) Giveon et al (2002) data. Here, the grids are shown only for κ = ∞-the grids for κ = 20 fully overlap these grids.…”
Section: The Ir Linesmentioning
confidence: 99%